Narasi-narasi Pengharaman Filsafat Oleh Kelompok Salafi Modern Indonesia (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
The research purposes that’s philosophy is still a topic of debate among Islamic groups. Modern salafi group is one of them with their narrative of rejection of philosophy. The author quotes the writings of Yasid Bin Abdul Kadir Jawas mentioning agnostic and polytheistic groups originating from the Greeks such as Plato and his followers, Aristotle and his followers. They discuss Allah Ta'ala by referring to their limited and corrupted mind without any support from The Prophet. The aim of this research is to explain modern Indonesian salafi groups narration which forbid philosophy. This type of research is field research using a qualitative descriptive approach, which utilizes qualitative data and is described descriptively. The result of this research is modern Indonesian salafi group rejects philosophy through several aspects, the narration they build is too textual, such as everything that the Holy Qur'an commands must be followed, because they have an understanding that philosophy was born from the Greeks, and these people are polytheists. Under this condition, they forbid philosophy, both Greek philosophy and Islamic philosophy. Keywords: Narration, Philosophy forbidding, Indonesian Modern Salafi.